Nickel-phytic acid hybrid for highly efficient electrocatalytic upgrading of HMF - Liu, Shuyi; Yuan, Xue; Huang, Xin; Huang, Yu; Sun, Chen; Qian, Kun; Zhang, Wenjie (Frontiers in Chemistry, 2023)
Electrocatalytic upgrading of 5-hydroxymethylfurfural (HMF) provides a promising way to obtain both high-value-added biomass-derived chemicals and clean energy. However, development of efficient electrocatalysts for oxidizing HMF with depressed side reactions remains a challenge. Herein, we report a nickel-phytic acid hybrid (Ni-PA) using natural phytic acid as building block for highly efficient electrocatalytic oxidation of HMF to 2,5-furandicarboxylic acid (FDCA). Due to the coordination of nickel ion and phosphate groups of phytic acid molecule, high selectivity and yield of FDCA were achieved at 1.6 V vs. RHE. Besides, Ni-PA has a higher electrochemical surface area and lower charge-transfer resistance than Cu/Fe-PA, which significantly promotes the oxidation of HMF to FDCA. This work demonstrates the potential of metal-phytic acid hybrids as effective electrocatalysts for biomass valorization.